Rural welfare implications of large-scale land acquisitions in Africa: A theoretical framework - Linda Kleemann; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2014)
Large-scale agricultural land acquisitions might entail substantial welfare implications for the affected rural population. Whether the impacts are indeed as devastating as the popular notion of land grabs would suggest depends on a number of factors, including the size of compensation payments, productivity spillovers on smallholders, employment opportunities for displaced farmers, and changes in food prices. We study the local welfare effects of land acquisitions in Sub-Saharan Africa using a theoretical model that captures the major channels through which land deals might affect rural African populations. We distinguish two basic scenarios. In the first scenario, the investor plants capital intensive staple food crops. Displaced farmers compete for a very limited number of jobs on the investment farm and spillovers to the remaining local farmers are rare. In the second scenario, where the investor is assumed to plant cash crops, potential spillovers through contract farming are larger and production is more labor intensive and hence provides better employment prospects. In both scenarios the crop produced on the investment farm is exported. The net welfare outcome varies with the relative strengths of the contradicting effects of spillovers, wages and food prices. We determine the minimum size of compensation payments for displaced farmers that would leave them as well off as staying on their plot.
Keywords: O13; Q12; 330; large-scale land acquisitions; local populations; welfare effects; displacement; food prices